PERBANDINGAN RASIO KEUANGAN PERBANKAN INDONESIA BERDASARKAN KELOMPOK BANK MENURUT BANK INDONESIA (BI) PERIODE TAHUN 2007 - 2013 - Viciwati Viciwati; Nur Aisyah F Pulungan (Universitas Mercu Buana, 2015)
After more than 10 years of economic crisis that makes the banking world collapsed then gradually slow start banking world might be improved. Various rules and regulations of Bank Indonesia adapted to the current state of the crisis with the intention that public funds are protected and the business climate in Indonesia can be run safely. The results of research that aims to look at the performance of banks for the period 2007 to 2013 show the performance of banks in Indonesia has improved this can be seen from the financial ratios include ROA, CAR, LDR, NPL and ROA which is in accordance with the ratio that is standardized by BI to each ratio were investigated. And for a group of banks surveyed the BPD group, and the mixture Bank Foreign Bank has assessed the performance is quite prominent due to the precautionary principle is applied properly it is also supported with sufficient capital and technology as well as a good human resoures. Keywords: Ratio of Banking, the bank group